2020
DOI: 10.1111/ans.16446
|View full text |Cite
|
Sign up to set email alerts
|

Pilonidal sinus: is histological examination necessary?

Abstract: Background Pilonidal sinus is a common pathology occurring in a number of sites including the gluteal cleft between the buttocks. Surgery is the principal mode of treatment with a variety of techniques proposed to cure the disease and prevent recurrence. The rate of malignant degeneration is estimated at 0.1% in patients with chronic pilonidal disease. A case series study of pilonidal sinus found that most patients with malignancy were over the age of 50 years and had had chronic pilonidal disease for several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
1
11
0
1
Order By: Relevance
“…14,15 In a recent study, Bacil ‘Otutaha et al reported that a routine histopathological examination of the pilonidal sinus material was unnecessary, but such an examination should be performed over the age of 50 years. 16 In our study, only 133 (5.3) of the 2486 patients were 50 years or older. The most common malignancy (90%) that develops on the basis of this disease is squamocolumnar carcinoma, but albeit rarely, basal cell carcinoma, sweat gland adenocarcinoma, and verrucous carcinoma have also been reported in the literature, mostly in the form of case reports.…”
Section: Discussionmentioning
confidence: 62%
“…14,15 In a recent study, Bacil ‘Otutaha et al reported that a routine histopathological examination of the pilonidal sinus material was unnecessary, but such an examination should be performed over the age of 50 years. 16 In our study, only 133 (5.3) of the 2486 patients were 50 years or older. The most common malignancy (90%) that develops on the basis of this disease is squamocolumnar carcinoma, but albeit rarely, basal cell carcinoma, sweat gland adenocarcinoma, and verrucous carcinoma have also been reported in the literature, mostly in the form of case reports.…”
Section: Discussionmentioning
confidence: 62%
“…Underlying clinical conditions, including diabetes mellitus or autoimmune disease, and patient factors, such as alcohol or tobacco usage and excessive pressure, are common causes of delayed wound healing. In our patient, bacterial wound infection and residual malignant lesion contributed to the chronic open wound [7,8]. Incomplete resection of the pilonidal disease could have added another causality.…”
Section: Discussionmentioning
confidence: 69%
“…In summary, a pilonidal sinus appeared after traumatic contusions, and the lesion progressed to malignant SCC. The short period for malignant transformation is notable, and mechanical and chemical injuries could have contributed to tissue alteration [7]. Imaging studies before the primary excision seemed to display a benign pilonidal cyst.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first case of malignant degeneration of pilonidal cyst described by Wolff in 1900 ( 24 ), the total number of reported cases in lituerature is fewer than 100. The most common histological type is squamous cell carcinoma, occurring in ~90% of cases ( 25 ).…”
Section: Discussionmentioning
confidence: 99%